Pengaruh Perencanaan, Pelaksanaan, dan Penatausahaan Laporan Pertanggung Jawaban Keuangan Dana Desa Terhadap Realisasi Pengelolaan APBDeS - Hamid Mukti Wibowo; Indra Lila Kusuma; Sri Laksmi Pardanawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to increase understanding of the influence of planing, implementation and administration on what has been realized by the APBDes, this research is included in the type of quantitative research. The population in this study includes all sub-districts in Nogosari sub-districts, Boyolali districts. The data analysis menthods used are validity tets, reliability test, normality test, multiple regression test, f tests, t test, coefficient of determination test. The reaults of this research show that planing influences APBDes management, implementation does not influences APBDes management, and administration influences APBDes management.